Lenvatinib Plus Pembrolizumab Versus Sunitinib in First-Line Treatment of Advanced Renal Cell Carcinoma: Final Prespecified Overall Survival Analysis of CLEAR, a Phase III Study - Motzer, Robert J; Porta, Camillo; Eto, Masatoshi; Powles, Thomas; Grünwald, Viktor; Hutson, Thomas E; Alekseev, Boris; Rha, Sun Young; Merchan, Jaime; Goh, Jeffrey C; Lalani, Aly-Khan A; De Giorgi, Ugo; et al. (Journal of clinical oncology, 2024)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical trial updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported.We present the final prespecified overall survival (OS) analysis of the open-label, phase III CLEAR study in treatment-naïve patients with advanced renal cell carcinoma (aRCC). With an additional follow-up of 23 months from the primary analysis, we report results from the lenvatinib plus pembrolizumab versus sunitinib comparison of CLEAR. Treatment-naïve patients with aRCC were randomly assigned to receive lenvatinib (20 mg orally once daily in 21-day cycles) plus pembrolizumab (200 mg intravenously once every 3 weeks) or sunitinib (50 mg orally once daily [4 weeks on/2 weeks off]). At this data cutoff date (July 31, 2022), the OS hazard ratio (HR) was 0.79 (95% CI, 0.63 to 0.99). The median OS (95% CI) was 53.7 months (95% CI, 48.7 to not estimable [NE]) with lenvatinib plus pembrolizumab versus 54.3 months (95% CI, 40.9 to NE) with sunitinib; 36-month OS rates (95% CI) were 66.4% (95% CI, 61.1 to 71.2) and 60.2% (95% CI, 54.6 to 65.2), respectively. The median progression-free survival (95% CI) was 23.9 months (95% CI, 20.8 to 27.7) with lenvatinib plus pembrolizumab and 9.2 months (95% CI, 6.0 to 11.0) with sunitinib (HR, 0.47 [95% CI, 0.38 to 0.57]). Objective response rate also favored the combination over sunitinib (71.3% v 36.7%; relative risk 1.94 [95% CI, 1.67 to 2.26]). Treatment-emergent adverse events occurred in >90% of patients who received either treatment. In conclusion, lenvatinib plus pembrolizumab achieved consistent, durable benefit with a manageable safety profile in treatment-naïve patients with aRCC.
Keywords: sunitinib; fenylmočovinové sloučeniny; Survival Analysis; Sunitinib; analýza přežití; nádory ledvin; humanizované monoklonální protilátky; Phenylurea Compounds; Carcinoma, Renal Cell; Antibodies, Monoclonal, Humanized; Kidney Neoplasms; Quinolines; lidé; chinoliny; Antineoplastic Combined Chemotherapy Protocols; Humans; karcinom z renálních buněk; protokoly protinádorové kombinované chemoterapie